The Impact of Incremental Innovation at Gojek Startup on Users in Batam City Using the Expectation Confirmation Model - Vincent, Vincent; Deu, Indasari; Eryc, Eryc (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2025)
In this modern era, the world has witnessed a phenomenal explosion in the growth of startups in various countries. Startups have become the main drivers of innovation and economic growth. Startup businesses are currently experiencing significant and rapid growth, especially in Indonesia. Currently, there are many new startup companies, so innovation is needed to compete with other competitors. Startup development requires creative ideas to attract investors. In addition to innovative ideas, product quality must also be a priority to attract consumer interest. Therefore, this study aims to examine the impact of incremental innovation on startups from the perspective of users in Batam City. The purpose of this study is to examine the impact of incremental innovation on the Gojek application. The author uses the Structural Equation Model (SEM) with the Partial Least Squares method, then the researcher applies the Extended Expectation Confirmation Model (ECM) from the perspective of Gojek application users to analyze the effect of incremental innovation efforts on the Gojek application. The author collects data by distributing questionnaires to people who have made transactions with Gojek. A total of 264 samples have been collected, and the results show that confirmation has a positive effect on the perception of enjoyment, satisfaction, and customer engagement. The results show that the perception of enjoyment and satisfaction has a positive impact on the user's intention to continue using the Gojek application. However, customer engagement does not significantly affect the user's intention to continue using the Gojek application.